Genetic characterization of human echinococcosis in Southern Punjab, Pakistan - Basharat, Nosheen; Khan, Jadoon; Ullah, Irfan; Shah, Aamer Ali; Ali, Ijaz (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Echinococcosis is a neglected tropical zoonotic infection that affects both the human and livestock populations. In Pakistan, the infection is long-standing, but data on its molecular epidemiology and genotypic characterization in the southern Punjab region are limited. The aim of the current study was the molecular characterization of human echinococcosis in southern Punjab, Pakistan. Methods Echinococcal cysts were obtained from a total of 28 surgically treated patients. Patients’ demographic characteristics were also recorded. The cyst samples were subjected to further processing to isolate DNA in order to probe the Nad1 and Cyt-b genes, followed by DNA sequencing and phylogenetic analysis for genotypic identification. Results The majority of the echinococcal cysts were from male patients (60.7%). The liver was the most commonly infected organ (60.71%), followed by the lungs (25%), spleen (7.14%), and the mesentery (7.14%). Molecular and genotypic identification through sequencing and phylogenetic tree analysis showed that most of the cysts (24/28, 85.7%) were caused by the species Echinococcus granulosus sensu stricto (E. granulosus s.s.) (G1 and G3), followed by Echinococcus multilocularis (E. multilocularis) and Echinococcus canadensis (E. canadensis) (G6/G7) (3/28, 10.8%, and 1/28, 3.5%, respectively). Conclusion The current study concluded that the majority of human infections were caused by E. granulosus s.s., followed by the E. multilocularis and E. canadensis species (G6/G7). Genotypic characterization among both human and livestock populations is needed to explore the genetic diversity of echinococcosis.